HIB-INFECTION: MENINGITIS, CELLULITIS IN THE CHILD OF 6 MONTHS - G. A. Harchenko; V. A. Kolokolov; O. G. Kimirilova; A. A. Kimirilov (Детские инфекции (Москва), 2015)
A clinical case of Hib-infection is the clinic purulent meningitis and pannikulita young child. Shows the complexity of the differential diagnosis of meningitis in combination with panniculitis with meningococcal disease (meningitis, meningokokktsemiya).